Exploring Values through Cooperative Integrated Reading and Composition - Suciana Wijirahayu; Armiati Armiati (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
Common problems faced by English as a Foreign Language (EFL) teachers in Indonesia especially in Junior high school level are developing students’ cognitive, affective, and psychomotor ability. Although there are supporting factors such as qualified teachers, appropriate basic teaching media, and supporting school environment, yet the issues have not been resolved. Cooperative Integrated Reading and Composition (CIRC) were applied in this study at one class of Al Qudwah Islamic Junior High School Depok to overcome some issues faced by the English teacher at the 8th grade. An action research was conducted to improve students comprehension in reading and writing. Integrative teaching media has been implemented as part of the efforts. Promising results was shown as the students were enthusiastic to gain information and critically discuss trending issues including the environment changes and social media. Religious values explored from the texts provided by the institution and selected by the students were reported in this study. Keywords: cooperative learning, critical reading, religious value, EFL